D-dimer and residual vein obstruction as risk factors for recurrence during and after anticoagulation withdrawal in patients with a first episode of provoked deep-vein thrombosis - Cosmi, Benilde; Legnani, Cristina; Cini, Michela; Guazzaloca, Giuliana; Palareti, Gualtiero (Thrombosis and Haemostasis, 2011)
D-dimer and residual venous obstruction (RVO) have been separately shown to be risk factors for recurrent venous thromboembolism (VTE) after a first episode of unprovoked proximal deep-vein thrombosis (DVT). It was the objective of this study to assess the predictive value of D-dimer and residual vein obstruction (RVO), alone and in combination, for recurrence after provoked DVT of the lower limbs. A total of 296 consecutive patients with a first episode of symptomatic provoked proximal DVT were evaluated at a university hospital in Bologna, Italy. On the day of anticoagulation withdrawal (T0), RVO was determined by compression ultrasonography. D-dimer levels (cut-off: 500 ng/ml) were measured at T0 and after 30 ±10 days (T1). The main outcome was recurrent VTE during a two-year follow-up. D-dimer was abnormal in 11.6% (32/276) and 31% (85/276) of subjects at T0 and at T1, respectively. RVO was present in 44.8% (132/294) of patients. Recurrence rate was 5.1% (15/296; 95% confidence interval [CI]: 3–8%; 3% patient-years; 95% CI: 2–5 %). An abnormal D-dimer either at T0 or at T1 was associated with an adjusted hazard ratio (HR) for recurrence of 4.2 (95% CI:1.2–14.2; p=0.02) and 3.8 (95%CI: 1.2–12.1; p=0.02), respectively, when compared with normal D-dimer. The HR for recurrence associated with RVO was not significant, and RVO did not increase the recurrence risk associated with an abnormal D-dimer either at T0 or T1. In conclusion, an abnormal D-dimer during vitamin K antagonist (VKA) treatment or at one month after VKA withdrawal is a risk factor for recurrence in patients with provoked DVT, while RVO at the time of anticoagulation withdrawal is not.
Keywords: Venous thromboembolism; D-dimer; recurrence; thrombophilia; vitamin K antagonists